Formulation and In Vitro Evalaution of Curcumin Loaded Solid Lipid Nanoparticles as Transdermal Drug Delivery - shinde, Naveen Polkal; Yegnoor Anand Kumar (Asian Journal of Pharmaceutical Research and Development, 2024)
The current research was to develop Curcumin loaded solid lipid nanoparticles (CUR-SLNs) by nano-emulsion template method using Span 60, Tween 60, Stearyl alcohol and Brij 35. CUR-SLNs were characterized for encapsulation efficiency, particle size and in vitro drug release. Further optimal formulation was incorporated into Carbopol gel and studied ex vivo permeation and skin irritation tests. The CUR-SLNs shows good encapsulation efficiency and desired particle size with prolonged drug release. The ex vivopermeation studies proved that CUR-SLNs considered to be a successful transdermal drug delivery system and provide a sustained release of encapsulated drug for 24 hr. Further, CUR-SLNs loaded carbopol gel considered to be non-irritant and safe to be applied on the skin for the intended period of time.